Penyimpangan-Penyimpangan dalam Penafsiran Al-Quran dan Efek Negatifnya Pada Aqidah Umat - Lufaefi, Lufaefi (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2018)
Al-Quran is a text that is free to be interpreted by anyone from its readers. As a dead text (unable to speak alone) allows itself to be interpreted according to the will of the interpreter. It is this background that gives rise to a variety of Koranic interpretations. However, it then also gives rise to forms of interpretation that come out of the ruling interpretation of the Koran, which later became known as deviant interpretations. Through research studies of Library, this paper will reveal forms of misinterpretation and negative effects for Muslims. This deviation of interpretation has extended to various modes of interpretation itself, such as being included in historical interpretations, theological opinions, Sufi interpretations, linguistic interpretations, scientific interpretations, even modern interpretations. These deviations have a devastating negative effect, such as assuming Islamic teachings are not authentic, mixing Islam with non-Muslims, misunderstanding the content of the Koran, and degrading salaf scholars.